1994
DOI: 10.1128/jvi.68.11.7040-7050.1994
|View full text |Cite
|
Sign up to set email alerts
|

A late adenovirus factor induces eIF-4E dephosphorylation and inhibition of cell protein synthesis

Abstract: Adenovirus prevents host cell protein synthesis during its late phase of replication in large part by causing the underphosphorylation of translation initiation factor eIF-4E, a component of initiation factor eIF-4F (cap-binding protein complex). Late adenovirus mRNAs are preferentially translated because they possess a reduced requirement for eIF-4F. This study continues the characterization of the mechanism by which adenovirus inhibits cellular protein synthesis. First it is shown that adenovirus blocks the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 76 publications
2
36
0
Order By: Relevance
“…The RNA is then cleared of ribosomes to allow replication to occur in the opposite direction. 57 This model is also likely to apply to other picornaviruses, as it has now been shown that PABP cleavage by PV 3C protease also inhibits translation directed by the PV IRES, both on RNAs with and without poly(A) tails. 58 It was also demonstrated that expression of a PABP that is resistant to cleavage by 3C protease within cells resulted in reduced production of viral RNA and reduced virus production.…”
Section: Picornavirusesmentioning
confidence: 96%
See 1 more Smart Citation
“…The RNA is then cleared of ribosomes to allow replication to occur in the opposite direction. 57 This model is also likely to apply to other picornaviruses, as it has now been shown that PABP cleavage by PV 3C protease also inhibits translation directed by the PV IRES, both on RNAs with and without poly(A) tails. 58 It was also demonstrated that expression of a PABP that is resistant to cleavage by 3C protease within cells resulted in reduced production of viral RNA and reduced virus production.…”
Section: Picornavirusesmentioning
confidence: 96%
“…It has also been shown recently that HAV 3C protease cleaves PABP in vivo and in vitro. 57 The resulting N-terminal cleavage product binds to the HAV 5 0 -UTR (to the pY1 region upstream of the IRES) and suppresses translation of the HAV mRNA. HAV does not induce host cell shutoff and infection does not result in cleavage of eIF4G.…”
Section: Picornavirusesmentioning
confidence: 99%
“…However, a highly structured sequence may allow mRNA translation under specific conditions. For instance, picornavirus mRNAs possess an internal ribosome entry site (IRES) that allows cap-independent translation during viral infection [20]. IRES structures are not restricted to viral mRNAs but have also been found in cellular mRNAs, such as human immunoglobulin heavy chain binding protein (BiP or Grp 78), which is also an HSP [21], human fibroblast growth factor 2 [22] and vascular endothelial growth factor (VEGF) [23], and some of them increase translation efficiency [23].…”
mentioning
confidence: 99%
“…It is interesting that the basal shunting activity identified in the absence of all three complementarity elements is found to be approximately 5% of the shunting efficiency of the original tripartite leader and considered to represent a basic shunt, the mechanism of which is unknown (34). The tripartite leader confers the ability to eliminate or gradually reduce the normal requirement for eIF4E or eIF4F (121,123). Late (123).…”
Section: Adenovirusmentioning
confidence: 99%
“…The tripartite leader confers the ability to eliminate or gradually reduce the normal requirement for eIF4E or eIF4F (121,123). Late (123). Significantly, ribosomal shunt mechanisms in adenovirus also function exclusively in conditions when elF4F is inactivated, during late adenovirus infection or heat shock conditions (33).…”
Section: Adenovirusmentioning
confidence: 99%